Hubungan Keteladanan Guru Pendidikan Kewarganegaraan dengan Motivasi Belajar Siswa SMA Santun Untan Kota Pontianak - Sitti Uswatun Hasanah (LPPM IKIP PGRI Pontianak, 2011)
Modeling the conditions that created and shaped throug a process of a series of behaviors that indicate the values of obedience, loyalty, regularity and order. In this case a teacher who perform exemplary compliance with regulations or order in the school, will exemplary view of the exemplary students that teachers do in performing their duties or compliance activity seen from teachers to the regulations established written or unwritten in himself a teacher.